Development diagnostic device of pin insulators - N. A. Tereshchenko; V. Yu. Miroshnik; M. A. Kholmov; K. I. Nikitin; B. N. Kovrizhin (Омский научный вестник)
The article proposes an invention to diagnose a damaged insulator under the operating voltage of the power line (VLEP), using leakage current control. There is made a prototype, experiments are carried out. The leakage current removed from the shunt design is converted to a digital signal for processing, transmission and further processing on the substation control room. The controlled leakage current corresponds to the magnitude of the insulation resistance of the insulator.